Mistakes and complications in the treatment of patients with distal humerus fractures - A. Bodnya; S. Dubovik (Kazimierz Wielki University, 2020)
Risks of complications in the treatment of humerus distal fractures are rather high.  This gives rise to a lot of controversy and, as a result, the need for research and development aimed at preventing errors and complications. Purpose: to study the structure of errors and complications being arisen in the treatment of patients with distal fractures of the humerus, and outline ways to eliminate them. Material and methods: A retrospective analysis of treatment outcomes was performed in 72 patients (52 men and 20 women, mean age 39.7 years) with distal humerus fractures. During treatment with the use of external osteosynthesis the errors and complications were identified in 43 patients (group I), 29 patients (group II) had error and complications after transosseous osteosynthesis. Results: Analysis of adverse treatment outcomes showed that in group I, diagnostic errors amounted to 2.3%, tactical errors - 11.6%, technical errors - 20.4%. In group II, only technical errors were noted and they accounts for 10.8%. Surgical treatment errors of this localization injuries led to the development of 23.3% of failures with external osteosynthesis, and 13.8% with transosseous osteosynthesis. Conclusions: a surgeon's qualification is the most important factor in distal humerus fractures patients treatment. This should include experience, application of optimal treatment tactics in each specific case, and anticipation of various complications development.